1999
DOI: 10.1097/00005392-199909010-00019
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and Progression in Low Grade Papillary Urothelial Tumors

Abstract: More than 90% of patients with stage Ta, WHO grade I have a benign form of bladder neoplasm, and few have truly malignant tumors. Future research should focus on reducing the number of recurrences and followup cystoscopies, and finding methods to identify malignant tumors so that pertinent treatment can be instituted. Subgrouping of WHO grade I bladder tumors as papillary neoplasm of low malignant potential and low grade papillary carcinoma seems to add valuable prognostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
73
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(85 citation statements)
references
References 19 publications
10
73
0
2
Order By: Relevance
“…Investigations over the past years have increased the understanding of the biological behavior of this disease and have led to novel prognostic and therapeutic recommendations and approaches (3). However, more than 50 to 70% of non-muscle invasive bladder cancer cases recur within 3 years after primary treatment with a 10 to 30% progression rate to muscle invasive tumor stages (pT2-pT4) (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations over the past years have increased the understanding of the biological behavior of this disease and have led to novel prognostic and therapeutic recommendations and approaches (3). However, more than 50 to 70% of non-muscle invasive bladder cancer cases recur within 3 years after primary treatment with a 10 to 30% progression rate to muscle invasive tumor stages (pT2-pT4) (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although these factors are relatively accurate in the group of patients with superficial UCC, improvement in the prediction of tumor recurrence in individuals is needed. [4][5][6] Many studies have investigated the prognostic potential of molecular markers to supplement or even replace the current standards.…”
mentioning
confidence: 99%
“…This new classification system recognizes papilloma, papillary neoplasm of low malignant potential (LMP), and low-grade papillary transitional cell carcinoma at the low-grade end of the transitional cell neoplasia spectrum. A recent study has shown that this new classification of low-grade bladder tumors can provide prognostic information (2).…”
mentioning
confidence: 99%